Leadership Style and Financial Literacy Strategies for Improving Business Performance and Sustainability in Food MSMEs - Lusianti, Dina; Karatri, Rhealin Hening; Fauziah, Farah Anissa (Jurnal Analisis Bisnis Ekonomi, 2024)
Total food and beverage MSMEs in Kudus is currently experiencing a decline. Therefore, this study analysed the role of leadership style and financial literacy in enhancing business performance and promoting sustainable development in the food MSMEs in Kudus, Central Java. A purposive sampling was used to choose 150 respondents, and data were analysed using the SEM-PLS method. The results showed leadership style and financial literacy impact positively and ly on business sustainability. Furthermore, leadership style and financial literacy positively and ly affected performance. Improved performance had a positive impact on sustainability, and served as a mediating factor in this study. To support sustainable practices, MSMEs leaders should integrate sustainability goals into their strategic planning, as both leadership style and financial literacy are essential in this effort. This could include applying eco-friendly practices, lowering waste, or investing in sustainable materials, all of which could improve brand image and attract conscious consumers.